PENGARUH ECO-ENZYME DAN PUPUK NPK TERHADAP PERTUMBUHAN TANAMAN SAWI PAHIT (Brassica juncea L.) - Faizi Nasution, Akbar Nur; Lestari, Widya; Yusida Saragih, Siti Hartati; Zamzami, Lutfi Fadillah (Agros Journal of Agriculture Science, 2024)
Brassica juncea L. or bitter mustard grows well in hot environments and is capable of producing fertile flowering seeds on its own. This research aims to determine the effect of providing eco-enzyme and NPK fertilizer on the growth of bitter mustard greens. The research was conducted in Ujung Bandar Labuhanbatu Village, Rantau Selatan, between January and March 2024. This research used a two-factor factorial randomized block design (RAK). First, the Mutiara NPK fertilizer factor with four levels: N0 as control, N1: 50 g/plant, N2: 75 g/plant, and N3: 100 g/plant. Second, the eco-enzyme factor with four levels: E0 as control, E1 25 ml/plant, E2: 50 ml/plant, and E3: 75 ml/plant. The research results showed that the combination of eco-enzyme and Mutiara NPK fertilizer had a significant effect on the growth of bitter mustard greens as indicated by the parameters of plant height, leaf area and number of leaves. A dose of 75 g of eco-enzyme and 50 ml of Mutiara NPK fertilizer is the best dose in providing the best influence on plant height, leaf area and number of bitter mustard leaves              Keywords: eco-enzyme; NPK mutiara; bitter mustard